PENERAPAN PRINSIP MENGENAL NASABAH PADA BANK PERKREDITAN RAKYAT BERDASARKAN PBI NOMOR 12/20/PBI/2010 - Nur Fitriyani (Faculty of Law, Maranatha Christian University, 2021)
ABSTRACT With the development of the BPR (Bank Perkreditan Rakyat) industry with the development of People's Credit Bank products and services, especially those based on information technology, the risk of using Rural Banks in money laundering and terrorism financing is getting higher. The prevailing provisions concerning the Application of Know Your Customer Principles (KYC) for Rural Banks need to be revised by referring to general principles that apply internationally in supporting efforts to prevent money laundering and prevent terrorism financing. so that the authors are interested in conducting research with the title: Implementation of Bank Indonesia Regulation Number 12/20 / PBI / 2010 in the Application of Know Your Customer Principles at Rural Banks. The creation of this journal is expected to provide an integral understanding of scientific concepts regarding the Application of Know Your Customer Principles at Rural Banks and contribute to ideas in the field of law in general and in particular in the field of banking law related to the application of the principle of knowing the customers of rural credit banks in the implementation of Bank Indonesia Regulation Number 12/20 / PBI / 2010. The method used in writing this journal is a normative research method with literature study through books, journal references, and laws and regulations that are relevant to the issues examined in the journal. Keywords: Customers, Indonesian Bank Regulations, People's Credit Banks.